The Church's Response to Childless Couples: Canonical and Pastoral Considerations on Sterility in the Ugandan context (c. 1084,§3) - Tumusiime, Sebastian Zanikire (Université d'Ottawa | University of Ottawa, 2017)
ABSTRACT Sterility is one factor which has the potential to disrupt the “partnership of the whole of life” (c. 1055, §1). In both Ugandan and Western societies, couples enter marriage with a strong desire to have children. In Western societies, childless couples seek medical tests and treatment for temporary infertility. Others who do not succeed in begetting children opt for the use of artificial means of reproduction. In developing countries such as Uganda, childless couples seek traditional means of enabling men to have children outside wedlock. It is noted that none of these options is approved by the Church. For this reason, canon 1084, §3, CIC 1983 which stipulates: “Sterility neither prohibits nor nullifies marriage” poses a challenge to apply. This thesis is an attempt to address the challenge and to make recommendations for the Church in Uganda. The first chapter discusses the development of the understanding of marriage as hierarchically ordered with procreation as the primary end. When the personalist dimension was incorporated into this understanding, procreation became one of the two ends of marriage: the good of the spouses and the good of children. However, in Uganda, procreation remains the primary end of marriage. As discussed in the second chapter, the good of the children is not always attained due to impotence and sterility. Since sterility is not an impediment to marriage, its potential to disrupt marital partnership is brought about by other canonical factors such as error, deceit and condition. These make sterility juridically relevant to the validity of marriage. With the advancement of science, sterile spouses may seek medical help in order to have a biological child. Out of the scientific means discussed in the third chapter, the Church accepts NaPro Technology, or any other means which treats the symptoms of infertility and enables conception to take place naturally. In the fourth chapter, this work discusses the Church’s documents which unequivocally state her stand on sterility and the use of artificial means of reproduction. In order to advance the teaching and legislation of the Church, recommendations are made for the Church in Uganda. It is hoped that by incorporating sterility in marriage preparation, integration of canon law to local marriage customs, and having functional and accessible tribunal services, it would be possible to address the questions raised by childless couples in the Ugandan context.
Keywords: Sterility